Visceral and Subcutaneous Fat Quality is Associated with Cardiometabolic Risk - Rosenquist, Klara J. (2013)
OBJECTIVE: The aim of this study was to evaluate whether computed tomography (CT) attenuation, as a measure of fat quality, is associated with cardiometabolic risk factors above and beyond fat quantity. BACKGROUND: Visceral (VAT) and subcutaneous adipose tissue (SAT) are pathogenic fat depots associated with cardiometabolic risk. Adipose tissue attenuation in CT images is variable, similar to adipose tissue volume. However, whether the quality of abdominal fat attenuation is associated to cardiometabolic risk independent of the quantity is uncertain. METHODS: Participants were drawn from the Framingham Heart Study CT sub-study. VAT and SAT volumes were acquired by semi-quantitative assessment. Fat quality was measured by CT attenuation and recorded as mean Hounsfield Units (HU) within each fat depot. Sex-specific linear and logistic multivariable regression models were used to assess the association between standard deviation (SD) decrease in HU and each risk factor. RESULTS: Lower CT attenuation of VAT and SAT was correlated with higher BMI levels in both sexes. Risk factors were generally more adverse with decreasing HU values. For example, in women, per 1-SD decrease in VAT HU, the odds ratio (OR) was increased for hypertension (OR 1.80), impaired fasting glucose (OR 2.10), metabolic syndrome (OR 3.65) and insulin resistance (OR 3.36) (all p<0.0001). In models that further adjusted for VAT volume, impaired fasting glucose, metabolic syndrome and insulin resistance remained significant. Trends were similar but less pronounced in SAT and in men. There was evidence of an interaction between HU and fat volume among both women and men. CONCLUSION: Lower CT attenuation of VAT and SAT is associated with adverse cardiometabolic risk above and beyond total adipose tissue volume. Qualitative indices of abdominal fat depots may provide insight regarding cardiometabolic risk independent of fat quantity.